2014
DOI: 10.1136/bmj.g4921
|View full text |Cite
|
Sign up to set email alerts
|

Subgroup analyses in randomised controlled trials: cohort study on trial protocols and journal publications

Abstract: listing only a study group name (the DISCO study group) rather than individual authors. The full author list has now been added to this paper and is also provided above.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
43
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(49 citation statements)
references
References 0 publications
5
43
0
1
Order By: Relevance
“…previous study that found 35% [11]. Finally, 21 (10%) of the RCTs changed the method used for data analysis.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…previous study that found 35% [11]. Finally, 21 (10%) of the RCTs changed the method used for data analysis.…”
Section: Discussionmentioning
confidence: 87%
“…Hence, it might have made a difference whether the research team was determined to find as many discrepancies as possible, or find as many explanations for potential discrepancies as possible. Another reason for the difference with two of the previous cohorts is that we included all available publications in the assessment, whereas these studies only included one publication for each trial protocol [9,11,23]. The third previous cohort study [10] had only a follow-up from IRB approval until publication of 5 years, which is likely too short to identify all relevant (additional) publications [30].…”
Section: Discussionmentioning
confidence: 99%
“…The results of post hoc sub‐group analyses could be used for hypothesis generation for future studies. For transparency, investigators should clearly describe the type of sub‐group analysis (hypothesis driven or post hoc) in trial registries, published study protocols and articles [Kasenda et al, ]. There are published criteria to help clinicians to assess the credibility of sub‐group analyses [Sun et al, ].…”
Section: Additional Analytical Considerationsmentioning
confidence: 99%
“…При отсутствии достоверных различий по первичному исходу в РКИ, поддерживаемых индустрией, чаще используется анализ подгрупп без детального описания гипотезы и тестирования взаимодействий [14,15]. Со-ответственно, анализ подгрупп должен выполняться со-гласно правилам и требует осторожности при форму-лировании заключения работы [16].…”
Section: фармацевтические компании и медицинская наукаunclassified